De-centring the interface. Towards the integrated study of interfacial relations - Lipp, Benjamin; Helm, Paula; Karafillidis, Athanasios; Pujadas, Roser (Information, communication & society, 2025)
Digital interfaces have become the primary way people relate to technology. While tangible and graphical user interfaces have long attracted scholarly attention, a variety of different interfaces connect cityscapes, homes, and brains with the digital realm. These connections may be lifesaving for some and a vehicle for invasive surveillance for others. Interfaces are thus also sites where layered relations, both digital and analogue, become translated, contested, and maintained. Furthermore, interfaces lie at the heart of new forms of machine-to-machine interaction and coordination. Software interfaces such as Application Programming Interfaces, have come to play a pivotal role in shaping platform economies, or automating entire sectors such as stock trading. Despite their ubiquity and variety, interfaces are largely reduced to a user-facing device, for example, a screen or a keyboard. In this article, we endeavour to go beyond this narrow notion of the interface. Drawing on an emerging body of literature that takes interfaces as the starting point for studies of the digital, we lay the groundwork for the integrated study of interfaces that conceptualises them as processual, distributed, and constitutively political. From this perspective, we focus not on what interfaces are but what they do. This shift towards processes of interfacing expands the scope of interface studies beyond the user-machine relation and towards the body-machine and machine-to-machine relation. Ultimately, we contend that interface studies must account for the layering of these interfacial relations.